Development of pulsed fibre lasers and supercontinuum light source based on nonlinear effect / Arman Zarei - Zarei, Arman (2015)
This thesis aims to investigate and demonstrate the generation of different types of pulse lasers and supercontinuum (SC) light based on nonlinear effects. At first, Brillouin fiber laser (BFL) is demonstrated using a long piece of Single mode fiber (SMF), Erbium-doped fiber (EDF) and highly nonlinear fiber (HNLF) as the gain medium. With 10 km long SMF, the BFL exhibits temporal characteristics where the pulse width and repetition frequency of the laser are obtained at 440 μs and 2 kHz, respectively. The Brillouin Erbium fiber laser (BEFL) also shows a self-pulsing characteristic with repetition rates of 66.7 kHz while mode-locked BFL is obtained by replacing the SMF with a 100m-long HNLF. Several passively mode-locked and Q-switched fiber lasers are then demonstrated based on nonlinear effects inside the ring laser cavity. For instance, a nanosecond optical pulse operating in fundamental mode is successfully generated in the EDF laser (EDFL) cavity by incorporating a 100 m long HNLF based on nonlinear polarization rotation (NPR) technique. The laser operates at 1567.2 nm and produced a pulse train with a repetition rate of 1.56 MHz, pulse width of 297 ns and the maximum pulse energy of 1.4 nJ. SC generation is then demonstrated by launching Q-switched mode-locking (QML), continuous-wave mode-locking (CWML) and dark pulse trains into various nonlinear fibers. With the amplified QML laser, the SC ranging from 1350 nm and 1900 nm has been successfully generated in 100 m long HNLF. With the amplified dark pulse, SC ranging from 1200 nm to 1810 nm, 1200 nm to 1920 nm and 1480 nm to 1740 nm are produced with the use of 50 m long photonic Crystal fiber (PCF), 100 m long HNLF and 20 km long PCF, respectively. Pulsed lasers have many applications in micromachining while super-continuum light sources are very useful for spectroscopy, frequency metrology, device characterization and medical science.